2011
DOI: 10.1227/neu.0b013e3182041992
|View full text |Cite
|
Sign up to set email alerts
|

History and Evidence Regarding Hydrostatic Shock

Abstract: This paper reviews the history and evidence related to remote wounding effects of ballistic pressure waves imparted to tissue by the impact of a bullet. Such remote effects are often referred to as hydraulic or hydrostatic shock. In spite of considerable published evidence and a long history, some medical professionals continue to regard the ability of a bullet to injure tissue that is not directly crushed or stretched as mythical (Jandial R, Reichwage B, Levy M, Duenas V, Sturdivan L. Ballistics for the neuro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Strong opinion was found dividing between papers suggesting the pressure wave contributes to wound injury5 10 4852 and those that it does not 9 19 37 44. Our review demonstrated that this opinion was based upon five papers describing original experimental data 5 10 51 53 54.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Strong opinion was found dividing between papers suggesting the pressure wave contributes to wound injury5 10 4852 and those that it does not 9 19 37 44. Our review demonstrated that this opinion was based upon five papers describing original experimental data 5 10 51 53 54.…”
Section: Resultsmentioning
confidence: 84%
“…Overall, 48 of the 59 original papers identified used experimental data derived from bullets; in contrast, there was a relative paucity of experimental data derived from explosive fragments (16/59 of papers). Although strongly expressed opinion was found as to the potential wounding effects of the pressure wave,5 10 4852 our review of the literature could not find objective evidence that this mechanism causes significant injury that either warrants, or enables, modelling at this stage.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The final form of ballistic wound is the generation of a hydrostatic shockwave, which is a controversial topic and of little relevance to the orthoplastic reconstructive surgical team [3,4]. However, this phenomena can rarely cause neuropraxia in nerves distant to the permanent and temporary cavities [5].…”
Section: Shockwavementioning
confidence: 99%